ANALISA PENGARUH VARIASI BEBAN PENGEREMAN DAN VARIASI KECEPATAN PUTAR (RPM) TERHADAP PERUBAHAN STRUKTUR MIKRO PIRINGAN CAKRAM DARI BAHAN AL ABU DASAR BATU BARA - Seputro, Harjo; Wijayanto, Arief (MEKANIKA: Jurnal Teknik Mesin, 2015)
Material cost and lightweight to be a requirement in the automotive world. This requirement led toinnovations in the manufacture of Metal Matrix Composite (MMC). Aluminum-based MMC with reinforcement Abucoal base developed as inputs for industries, especially the automotive industry because the material is cheap andeasy to come by in the can. The purpose of this study to determine the influence braking loads and rotational speedvariai to change the microstructure of the base material disk disc al - ash coal. The research activities begins theprocess of making a composite with the method of HAS, then how is generated into a disk disc, the next disc-discdiperlakuan T6 heat, further testing with load variations braking and speed, turn while braking loads are used 3kg,4kg, 5kg and with the rotational speed 600rpm , 700rpm, 800rpm. The test results braking ratio of disc-disc originalwith disk disc al - bottom ash coal in comparison type of disc discs al - bottom ash coal produces a highertemperature than the disc-disc original because of the heat capacity on the disc al - bottom ash coal is greatercompared to the original disk disc. So that the braking load variations and variations in rotational speed (rpm), themicro structure changes that occur are from the compound turned into Al2SiO4 Al2MgSiO4 these changes occur asa result of the heat that builds up during braking.Keywords : composites, variation of speed, braking loads, microstructure.